2022
DOI: 10.1002/pros.24320
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood deprivation and risk of mortality among men with prostate cancer: Findings from a long‐term follow‐up study

Abstract: Background: The overall survival rate of prostate cancer (PCa) has improved over the past decades. However, huge socioeconomic and racial disparities in overall and prostate cancer-specific mortality exist. The neighborhood-level factors including socioeconomic disadvantage and lack of access to care may contribute to disparities in cancer mortality. This study examines the impact of neighborhood deprivation on mortality among PCa survivors.Methods: North Carolina-Louisiana Prostate Cancer Project (PCaP) data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 55 publications
(118 reference statements)
1
4
0
Order By: Relevance
“…After adjusting for known confounders including comorbidities and cancer stage, higher ADI remained associated with worse local control and overall survival in our cohort, suggesting that higher ADI was independently associated with poorer oncologic outcomes. These findings, to our knowledge, have not been reported previously for NPC, and are consistent with previous studies that have demonstrated the association of low SES with worse outcomes in other cancers such as oral cavity, breast, colorectal, prostate, and lung cancers 9–11,14,15 . Our results contribute to the growing body of literature highlighting the importance of addressing disparities in cancer outcomes related to SES and neighborhood disadvantage.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…After adjusting for known confounders including comorbidities and cancer stage, higher ADI remained associated with worse local control and overall survival in our cohort, suggesting that higher ADI was independently associated with poorer oncologic outcomes. These findings, to our knowledge, have not been reported previously for NPC, and are consistent with previous studies that have demonstrated the association of low SES with worse outcomes in other cancers such as oral cavity, breast, colorectal, prostate, and lung cancers 9–11,14,15 . Our results contribute to the growing body of literature highlighting the importance of addressing disparities in cancer outcomes related to SES and neighborhood disadvantage.…”
Section: Discussionsupporting
confidence: 93%
“…The AJCC 8th edition stage distribution was as follows: 30 patients (6.0%) were stage I; 81 (16.1%) were stage II; 189 (37.6%) were stage III; and 203 (40.4%) were stage IVA. Patients from higher ADI neighborhoods 6–10 were more likely to present with advanced‐stage disease (AJCC stage III/IVA) compared to patients with low ADI, 1–5 at 87% versus 76% ( p = 0.03).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Few of the previous studies 25,26 that investigated neighborhood deprivation and prostate cancer had the diversity of our cohort. Consistent with these and other studies, 15,27 increased neighborhood deprivation tends to be associated with metastatic and lethal prostate cancer rather than the localized disease.…”
Section: Fine and Gray Cox Proportional Hazardsmentioning
confidence: 99%
“…37,38 Furthermore, we could not examine whether census tract characteristics were associated with individual-level characteristics using our survey. Because we lack participants' addresses over time, we were unable to examine longitudinal changes, time-varying associations, changes in participant mobility, or the role of deprivation at other known important JAMA Network Open | Equity, Diversity, and Inclusion neighborhood levels (eg, block 26 or zip code 39 ). Furthermore, our study lacks data on prostate cancer screening among participants, which is a factor associated with a prostate cancer diagnosis; therefore, we were not able to adjust for this potential confounder.…”
Section: Strengths and Limitationsmentioning
confidence: 99%